2021
DOI: 10.1155/2021/5581570
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxidative Stress in Hypertensive Disorders of Pregnancy (Preeclampsia, Gestational Hypertension) and Metabolic Disorder of Pregnancy (Gestational Diabetes Mellitus)

Abstract: Purpose of the Review.To highlight the role of oxidative stress in hypertensive disorders of pregnancy (HDP) and metabolic disorders of pregnancy (gestational diabetes mellitus). Recent Findings. In both preeclampsia (PE) and gestational hypertension (GH), oxidative stress leads to inadequate placental perfusion thus resulting in a hypoxic placenta, which generally leads to the activation of maternal systemic inflammatory response. In PE, this causes inflammation in the kidneys and leads to proteinuria. A prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(73 citation statements)
references
References 101 publications
1
70
0
2
Order By: Relevance
“…Gestational diabetes mellitus (GDM) and preeclampsia (PE) are common complications in pregnancy with similar risk factors, including obesity, advanced age, and multiple pregnancy (1,2). Moreover, in both GDM and PE, the pathophysiological processes involve oxidative stress, pro-inflammatory factor release, vascular endothelial dysfunction (3,4), which all increase the risk of future maternal diabetes and cardiovascular disease (5)(6)(7)(8); thus, a correlation between GDM and PE may exist.…”
Section: Introductionmentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM) and preeclampsia (PE) are common complications in pregnancy with similar risk factors, including obesity, advanced age, and multiple pregnancy (1,2). Moreover, in both GDM and PE, the pathophysiological processes involve oxidative stress, pro-inflammatory factor release, vascular endothelial dysfunction (3,4), which all increase the risk of future maternal diabetes and cardiovascular disease (5)(6)(7)(8); thus, a correlation between GDM and PE may exist.…”
Section: Introductionmentioning
confidence: 99%
“…Two prospective cohort studies [ 64 , 65 ] and four RCTs [ 66 , 67 , 68 , 69 ] evaluated in vivo effects of melatonin administered from the cycle preceding the IVF attempt. It was shown that melatonin reduced the number of degenerated oocytes [ 64 , 69 ], increased the number of mature oocytes [ 66 , 69 ], and increased fertilization rate [ 65 ] and embryo quality [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two prospective cohort studies [ 64 , 65 ] and four RCTs [ 66 , 67 , 68 , 69 ] evaluated in vivo effects of melatonin administered from the cycle preceding the IVF attempt. It was shown that melatonin reduced the number of degenerated oocytes [ 64 , 69 ], increased the number of mature oocytes [ 66 , 69 ], and increased fertilization rate [ 65 ] and embryo quality [ 69 ]. One RCT [ 68 ] failed to detect any significant differences in cumulative pregnancy rate or oocyte and embryo parameters, but the authors recognized that the study was not sufficiently powered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic syndrome is one of the representatives of increased complications in pregnant women with euthyroid status [ 11 ]. Metabolic syndrome is resulted from abnormal chemical reactions in the body, which contributes to numerous gestational diseases, including gestational diabetes mellitus [ 12 ], gestational hypertension [ 13 ], gestational hypothyroidism [ 14 ], etc. Metabolic disorder also exerts direct adverse effects to the progress and outcome of pregnancy [ 15 ].…”
Section: Introductionmentioning
confidence: 99%